Shopaholic Phenomenon, Choice of Shopping Place and the Development of Megamalls in Ibadan, Nigeria (2021)
Shopping activities in the 21st century are taking a social dimension rather than mere commercial activities.This is evident in the importance of consumer attachment to shopping and choice of shopping place, which necessitated the increase in the number of megamalls in many cities globally, including Nigeria. This study examined the shopaholic phenomenon, choice of shopping place, and the development of megamalls in Ibadan, Nigeria. The study was empirical using both quantitative and qualitative methods for data collection. Two hundred sixteen copies of the questionnaire were administered to mall customers, while an In-depth interview was conducted for six mall operators cut across malls in Ibadan. Statistical Package for Social Sciences using frequency tables, percentages, and histogram charts was used for analysis. The study revealed that most respondents choose Megamall as their shopping place, and there is a connection between the shopaholic phenomenon, choice of shopping place, and the development of megamalls. The conducive and serene environment which megamalls portray has wooed many customers in the urban areas to choose it as their priority as it concerns shopping, and that has gone a long way to enhance the development and sustainability of megamalls in Nigeria. Most customers patronize malls because of their innate love of shopping, ostentatious life, and showy life to impress friends and well-wishers. The glamour and fascination that megamalls display cannot be gotten in retail shops or open markets. Customers are delighted with their experiences in the megamalls that account for their continued patronage of the megamalls over other shopping alternatives